Cheese whey wastewater: Characterization and treatment - Carvalho, Fátima (2013)
Cheese whey wastewater (CWW) is a strong organic and saline effluent whose characterization and treatment have not been sufficiently addressed. CWW composition is highly variable due to raw milk used, the fraction of non valorized cheese whey and the amount of cleaning water used. Cheese whey wastewater generation is roughly four times the volume of processed milk. This research tries to conduct an exhaustive compilation of CWW characterization and a comparative study between the different features of CWW, cheese whey (CW), second cheese whey (SCW) and dairy industry effluents. Different CWW existing treatments have also been critically analyzed. The advantages and drawbacks in aerobic/anaerobic processes have been evaluated. The benefits of physicochemical pre-stages (i.e. precipitation, coagulation–flocculation) in biological aerobic systems are assessed. Pre-treatments based on coagulation or basic precipitation might allow the application of aerobic biodegradation treatments with no dilution requirements. Chemical precipitation with lime or NaOH produces a clean wastewater and a sludge rich in organic matter, N and P. Their use in agriculture may lead to the implementation of Zero discharge systems.